2017
DOI: 10.25159/0027-2639/991
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of E-Records Readiness at the Ministry of Labour and Home Affairs, Gaborone, Botswana

Abstract: This study sought to assess electronic records (e-records) readiness at the Ministry of Labour and Home Affairs (MLHA), Gaborone, Botswana, within the purview of the implementation of an e-records management solution – the National Archives and Records Management System (NARMS). The assessment was done using tenets derived from the existing International Records Management Trust (IRMT) E-records Readiness Tool. The assessment examined the national legal and policy framework, compliance with policies, standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…This could be attributed to lack of appreciation of the importance of managing records. The study concurs with Moalthod and Kalusopa (2016) who reported that only 45% of staff were aware of e-records management at the Botswana Ministry of Labour Headquarters due lack of orientation programme. Increasing awareness campaigns about records management programme help users understand the deliberate procedures and their responsibilities for managing e-records.…”
Section: Internal and Public Awareness Of E-records Management Programmesupporting
confidence: 90%
See 2 more Smart Citations
“…This could be attributed to lack of appreciation of the importance of managing records. The study concurs with Moalthod and Kalusopa (2016) who reported that only 45% of staff were aware of e-records management at the Botswana Ministry of Labour Headquarters due lack of orientation programme. Increasing awareness campaigns about records management programme help users understand the deliberate procedures and their responsibilities for managing e-records.…”
Section: Internal and Public Awareness Of E-records Management Programmesupporting
confidence: 90%
“…They support business functions and are critical for the assessment of both government and private performance (Mnjama and Wamukoya, 2004). E-records also support effective transparency and accountability in decision making thereby contributing to national development (Moalthodi and Kalusopa, 2016),). Due to such benefits, sound management of electronic records and print records has increasingly become a topical issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These e-records require electronic records management systems (ERMS) or electronic records and document management systems (EDRMS), which will enable them to be managed, used, stored and effectively preserved (Mutimba, 2014; Records Solutions, 2010). ERMS ensure effective management of resources, minimizes litigation risks, improves accountability and transparency and provides the basis for complying with legal requirements (Abuki, 2014; Coetzer, 2012; Moatlhodi, 2015; Sebina and Zulu, 2014; Zulu et al , 2012). Therefore, managers should adopt appropriate strategies for successful implementation of ERMS.…”
Section: Introductionmentioning
confidence: 99%
“…In such a scenario, the use of the cloud for records management cannot thrive as it depends on the Internet to operate. Moatlhodi and Kalusopa (2016) aver that lack of capacity for records management staff to manage records in an electronic environment was an impediment to the implementation of the National Archives and Records Management System (NARMS) in the then Ministry of Labour and Home Affairs in Botswana. Lack of capacity to manage electronic records is not limited to Botswana as it is also common across the ESARBICA region (Kemoni 2009;Mnjama & Wamukoya 2007;Mosweu & Kenosi 2018).…”
Section: Summary On the Implications Of Cloud-computing Services In Records Management In Africamentioning
confidence: 99%